(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
In this article, the scientific theoretical basis for improving the practice of financial market regulation is widely covered. The article discusses in detail the essence, important aspects of regulation of the country’s financial market, methods of regulation, and developed scientific proposals for improving the regulation of the financial market.